Classification of theoretical and methodological foundations of training future coaches - Chopyk T.V (Kharkov National Pedagogical University, 2013)
The problem of training future trainers and teachers in higher education institutions is considered. Theoretically analyzed the problem of training future coaches. Systematized content of theoretical and methodological foundations of training future coaches. It was revealed that the system of knowledge creation is based on logically related topics of general characteristics of the professional activity of the future coaches and features of the content of the production functions. Also on the justification of typical tasks of future coaches, definition and development of professional competencies of future coaches during training. In addition, also the prospects for the development of sport as a future profession. The proposed classification is different from previous work defining the future of professional competence of trainers and teachers in the process of training, clarifying sections of future performance professional coaches and prospects of the development of sports.